Making districts functional for universal health coverage attainment: lessons from Ghana - Karamagi, Humphrey Cyprian; Sy, Sokona; Kipruto, Hillary; Kembabazi, Bertha; Kidane, Solyana Ngusbrhan; Moyo, Thandekile Ntombikayise; Titi-Ofei, Regina; Atweam, Dominic; Debpuur, Cornelius; Ofosu, Anthony; Kasolo, Francis Chisaka (Frontiers in Public Health, 2023)
Ensuring the sub national level in the health system can function effectively is central to attainment of health results in countries. However, the current health agenda has not prioritized how districts can deploy their existing resources effectively, to maximise the efficiency equity and effectiveness in their use. Ghana initiated a self-assessment process to understand the functionality of districts to deliver on health results. The assessment was conducted by health managers in 33 districts during August – October 2022 using tools pre-developed by the World Health Organization. Functionality was explored around service provision, oversight, and management capacities, each with defined dimensions and attributes. The results showed a lack of correlation between functionality and performance as is currently defined in Ghana; a higher functionality of oversight capacity compared to service provision or management capacities; and specifically low functionality for dimensions relating to capacity to make available quality services, responsiveness to beneficiaries and the systems & structures for health management. The findings highlight the need to shift from quantitative outcome indicator-based performance approaches to measures of total health and wellbeing of beneficiaries. Specific functionality improvements are needed to improve the engagement and answerability to the beneficiaries, investments in access to services, and in building management architecture.